Melacak Makna Identitas Budaya: Kasus Budaya Sunda - Maman Suharman, Thomas (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2005)
Crisis of identity and the search for identity is a typical phenomenon of modern culture. Sundanese culture, one of many other Indonesian cultural tribes, is not an exception. Referring to the idea offered by Pierre Buhler, the article will argue that crisis is needed, because it exhilarates the search for identity for the sake of survival vis a vis the challenges of modernity. In the process, the society is not supposed to attach itself solely to its objective-material references, because if so, the search for identiy will come to a dead end, Sundanese identity will be closed. Whereas, identity is a dynamic process, and as such it should be open to any critical evaluation, that enables it to develop. In order to develop, objective references that constitute the identity of Sunda (or that of any other Indonesian tribal culture), which in this modern age are increasingly falling off, should be countered by subjective-spiritual references. But the subjective search, in turn, should be warranted so that it may not fall into pure subjectivism, which may hamper the identity development. Therefore, identity should be confronted to objectivity. This would mean taking into consideration, with confidence and belief, what the other people will say about Sunda; putting this belief into discourse which can be evaluated with critical mind, and evaluating its practical importance in the implementation of Sundanese ethical virtues.